Composition of Regenerated Cell Walls of Reverting Aureobasidium pullulans Protoplasts - Quigley, David R. (1984)
Protoplasts of Aureobasidium pullulans, formed by treating normal blastospores with polysaccharide-hydrolyzing enzymes, synthesized glycans when incubated in shallow culture. The polysaccharides formed a loose, thick coating on the cells. The glycans that were formed are similar to the glycans in normal cell walls; however, they lack the branching that is normally found. This result is consistent with the findings of others who have studied the cell wall composition of reverting yeast protoplasts.